A Relatively New Form of Theology: Reception of the Methodological Transformation of «Gaudium et spes» in the United States - Schickendantz, Carlos (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2020)
A methodological novelty emerged in the process of drafting Gaudium et spes that ultimately structured the Pastoral Constitution. According to Marie-Dominique Chenu, in the discernment of the signs of the times resides «the soul of the scheme». He refers to the «empirical-theological approach» (M. McGrath) that «marks a new era of theology» (H.-J. Sander). This article analyzes the reception of this methodological transformation in the bibliography produced in the United States. Several questions guide this essay. First and foremost, the study of the awareness of this methodological change. It is also considered the conceptualization and the bibliographic sources used, and the hermeneutical perspectives that support the various points of view. As a result, it is possible to outline some peculiarities strongly conditioned by the linguistic context.